Pengaruh Motivasi Kerja, Disiplin Kerja dan Kompensasi terhadap Kinerja Karyawan Badan Pendapatan Daerah Kota Semarang (Studi Pada Badan Pendapatan Daerah Kota Semarang) - Yogi Dwi Prasetyo; Sri Isnowati (Universitas Batanghari, 2022)
This study aims to determine the effect of work motivation, work discipline and compensation on the performance of employees of the Regional Revenue Agency Semarang City. This type of research used is quantitative with a population. The data collection technique was carried out by distributing questionnaires to 100 respondents to help answer questions on the distributed questionnaire. Then, quantitative data analysis was carried out, namely validity and reliability tests, classical assumptions and multiple regression analysis, wherever hypothesis testing was carried out through t-test and F-test. The results of this study indicate that work motivation has a positive effect on the performance of employees of the Regional Revenue Agency, work discipline has a positive effect on the performance of employees of the Regional Revenue Agency and compensation has a positive effect on the performance of employees of the Regional Revenue Agency Semarang.